Analisis Perhitungan Harga Pokok Penjualan Menggunakan Metode Full Costing untuk Meningkatkan Laba pada Usaha Ketupat Sayur Betawi Bang Asep Jakarta Barat: Analysis of the Calculation of Cost of Goods Sold Using the Full Costing Method to Increase Profits in the Betawi Vegetable Ketupat Business Bang Asep West Jakarta - Aliya Khoirunnisa; Najwa Atsanti; Nadine Paxia Winaya; Devina Nasya Fitriani; Azzahra Azzah Fazirah (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to analyze the calculation of the cost of goods sold using the Full Costing method at Ketupat Sayur Betawi Bang Asep, a micro and small enterprise located in West Jakarta. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The analyzed data consisted of raw material costs, direct labor costs, and production overhead costs during March 2026. The findings indicate that the business owner still applies a simple costing system that does not fully incorporate all production cost components. Using the Full Costing method, the total production cost was Rp779,500 for 60 portions, resulting in a production cost of Rp13,000 per portion. In contrast, the existing method generated a production cost of Rp10,000 per portion. These results demonstrate that the Full Costing method provides more comprehensive and accurate cost information by including all production cost elements. Therefore, its implementation can support more appropriate pricing decisions, improve cost control, and enhance profit management.